Acetylsalicylic Acid Daily vs Acetylsalicylic Acid Every 3 Days in Healthy Volunteers: Effect on Platelet Aggregation, Gastric Mucosa, and Prostaglandin E2 Synthesis. (27th January 2016) - Ferreira, Plinio Minghin Freitas; Gagliano‐Jucá, Thiago; Zaminelli, Tiago; Sampaio, Marinalva Ferreira; Blackler, Rory Willian; Trevisan, Miriam da Silva; Novaes Magalhães, Antônio Frederico; De Nucci, Gilberto
Abstract: Substantial platelet inhibition was observed 3 days after a single administration of acetylsalicylic acid 81 mg to healthy volunteers. Here we investigate prostaglandin E2 (PGE2 ) antrum concentrations and gastrointestinal symptoms in two treatment groups: one receiving losartan and acetylsalicylic acid every day and the other receiving losartan every day and acetylsalicylic acid every 3 days. Twenty‐eight healthy volunteers from both sexes received either 50 mg losartan and acetylsalicylic acid 81 mg daily or 50 mg losartan and acetylsalicylic acid 81 every 3 days with placebo on the other days. Therapy was delivered for 30 days for both groups. Gastric endoscopy was performed before and after treatment period. Biopsies were collected for PGE2 quantification. Platelet function tests were carried out before and during treatment and TXB2 release on platelet rich plasma was measured. The every 3 day low‐dose acetylsalicylic acid regimen produced complete inhibition of platelet aggregation compared to the daily treatment. Thromboxane B2 release was substantially abolished for both groups during treatment. There was no significant difference on the endoscopic score of both treatment groups after the 30‐day treatment ( P = .215). There was over 50% suppression of antrum PGE2 content on volunteers receiving acetylsalicylic acid daily ( P = .0016), while for the every 3 day dose regimen there was no significant difference between pre and post‐treatment antrum PGE2 dosages ( P = .4193). Since PGE2 is involved in gastric healing, we understand that this new approach could be safer and as efficient as the standard daily therapy on a long‐term basis.